Knowledge and practices of nursing professionals in pressure injury prevention and care - Francisca Débora Veras Silva; Priscila Cristina da Silva Thiengo de Andrade; Eugenio Fuentes Perez Júnior; Ariane da Silva Pires; Cristiane Helena Gallasch (Universidade Federal de Santa Maria, 2019)
Objective: to identify the knowledge of the nursing staff about multiple factors that may predispose to development and imply to the care of pressure ulcers in hospitalized patients admitted in clinical units. Method: descriptive study with mixed method, with data collected between 2018 April and July, in a university hospital in Rio de Janeiro, with 47 nursing professionals. After approval by the Research Ethics Committee, the tool "Instrumento para Identificação do Nível de Conhecimento Sobre Úlcera de Pressão e Medidas Preventivas" was applied, with results analyzed by descriptive and inferential statistics. Latter, participants answered a semi-structured interview, evaluated through content analysis. Results: a knowledge deficit related to injury prevention was identified. Regarding care, there is prejudice related to the lack of human and material resources. Conclusion: permanent in-service education about these issues are necessary, as well as the guarantee of human and material resources.